PENGARUH WILAYAH KERJA DAN TUNJANGAN JABATAN TERHADAP KINERJA PERANGKAT DI KECAMATAN JETIS MOJOKERTO - Kun Setiyono (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
Analysis of the performance of the device requires a measure of performance based on results that are balanced to measure success in meeting goals and objectives. Performance measurement is based on the function of the work area and allowances is a useful tool in the effort to achieve the goal. Through the assessment process work areas and allowances can provide objective assessment in the achievement of the performance of the device, so it helps in management decision making. This type of research is quantitative by using a sample of 91 devices in Jetis Mojokerto. This source of research data obtained from the respondents' answers on the questionnaire were then analyzed using multiple linear regression analysis. The results showed that the first hypothesis is empirically proven that working areas and allowances simultaneously significant effect on the performance of the device in Jetis Mojokerto. Further testing in partial work area has no significant effect on the performance of the device, but the office allowances significant effect on the performance of the device in Jetis Mojokerto. This has some consequences allowances have a dominant influence on the device performance than variable working area.